Tumor invasion front in oral squamous cell carcinoma - Cuevas-González, Juan Carlos (2022)
Oral squamous cell carcinoma is a neoplasm that originates from the epithelial mucosa. It is usually more frequent between the fifth and sixth decades of life, and more than 90% of carcinomas of the oral cavity are squamous cell carcinoma. It is an invasive neoplasia with a significant recurrence rate; 40% of patients present with metastases in the cervical lymph nodes at the time of diagnosis. The tumor invasion front is a characteristic of tumor growth, which can be infiltrative or noninvasive